2021
DOI: 10.3390/s21196595
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based Analysis of Face Images as a Screening Tool for Genetic Syndromes

Abstract: Approximately 4% of the world’s population suffers from rare diseases. A vast majority of these disorders have a genetic background. The number of genes that have been linked to human diseases is constantly growing, but there are still genetic syndromes that remain to be discovered. The diagnostic yield of genetic testing is continuously developing, and the need for testing is becoming more significant. Due to limited resources, including trained clinical geneticists, patients referred to clinical genetics uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The various architectures of CNN itself successfully identify diseases from various medical images because of the high frequency and excellent recognition rate [35]. So, of course, in the last five years, many studies have focused on the development of CNN in detecting genetic diseases through facial recognition [7], [20], [36]- [40]. Developments also lead to more complex problems, whereas Singh and Kisku in 2018 [36] and Gurovich et al in 2019 [37] have identified various genetic diseases and the results obtained are pretty good.…”
Section: Deep Learning-based Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The various architectures of CNN itself successfully identify diseases from various medical images because of the high frequency and excellent recognition rate [35]. So, of course, in the last five years, many studies have focused on the development of CNN in detecting genetic diseases through facial recognition [7], [20], [36]- [40]. Developments also lead to more complex problems, whereas Singh and Kisku in 2018 [36] and Gurovich et al in 2019 [37] have identified various genetic diseases and the results obtained are pretty good.…”
Section: Deep Learning-based Methodsmentioning
confidence: 99%
“…The results of this study get an accuracy of 84%, where the model can detect abnormalities without requiring information about specific abnormalities. The system does not have to be trained with all genetic diseases to detect genetic features on existing faces [40]. A summary of all the research described can be seen in Table 1.…”
Section: Deep Learning-based Methodsmentioning
confidence: 99%
“…M. Geremek and K. Szklanny in [ 9 ] investigated deep learning based detection of genetic diseases from face images, for 15 genetic disorders associated with facial dysmorphism. The authors achieved 84% accuracy for 15 classes, and up to 96% for binary classification of particular diseases.…”
Section: Overview Of the Contributionsmentioning
confidence: 99%
“…Sim G, as mentioned in Equation (11), is their similarity based on the GM only, and Sim L is their combined similarity at the point of consideration. Sim L is measured by the relation given in Equation (12).…”
Section: Ssi M(pmentioning
confidence: 99%
“…The formulation of face sketches based on learning from the reference photos and their corresponding forensic sketches has been an active field since the last two decades [12,13]. It helps the law enforcement agencies in the search, isolation, and identification of suspects by enabling them to match sketches against possible candidates from the mug-shot library [14][15][16] and/or photo dataset of the target population [17,18].…”
Section: Introductionmentioning
confidence: 99%